Efektifitas Serbuk Daun Tagetes erecta Linnaeus untuk Mengendalikan Nematoda Bengkak Akar (Meloidogyne spp.) pada Tanaman Tomat (Lycopersicum esculentum Mill.): english - Trismal, Okiel; Busniah, Munzir; Winarto, Winarto (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2018)
Tagetes erecta Linnaeus is classified as a nematisidal plant so that it can control root-knot nematodes (Meloidogyne spp.). The purpose of this study was to determine the dose of T. erecta leaf powder, which was effective in controlling root-knot nematodes (Meloidogyne spp.) on tomato. This study used a Completely Randomized Design (CRD) with six treatments and four replications, namely the effectiveness of several doses of T. erecta leaf powder (control/ no treatment, 5 g, 10 g, 15 g, 20 g, 20 g, 25 g each 5 kg of soil). The results showed that the application of T. erecta leaf powder reduced the amount of root-knot, number of eggs and groups of eggs and the number of nematodes in the soil. The most effective dose was 20 g/ 5 kg of soil.